THE EFFECTS OF EXERCISE TRAINING ON CARDIOVASCULAR REGULATION IN INDIVIUALS WITH SPINAL CORD INJURY - DITOR, DAVID (My University, 2003)
Introduction. Individuals with spinal cord injury (SCI) are prone to severe cardiovascular dysfunction and an increased risk of mortality from various cardiovascular diseases. The underlying mechanisms responsible for the increased cardiovascular risk are not precisely understood, however, the reduced activity levels that accompany SCI certainly contribute. Unfortunately, muscular paralysis (partial or complete) limits the exercise options for individuals with SCI and the role of exercise rehabilitation as a means of reversing cardiovascular risk is not fully understood in this population. Recently developed methods may be particularly useful in evaluating the effects of exervise on the cardiovascular health and function in individuals with SCI. Specifically, power spectral analysis of heart rate variability (HRV) and blood pressure variability (BPV) have become commonly used, non-invasive methods used to quantify the autonomic control of the cardiovascular system. Clinically, measures of HRV and BPV have particular value as relatively decreased cardiac vagal predominance has been associated with an increased risk of cardiovascular mortality, and increased BPV is associated with end organ damage. In addition, Doppler ultrasound imaging techniques allow for the determination of arterial dimension and function. As such, these imaging techniques may be used to determine arterial blood flow and vascular compliance; the latter referring to the ability of the vessel to expand and recoil during changes in intravascular pressure. Clinically, these measures are also of value as reductions in blood flow contribute to thrombus formation, in addition to delayed wound healing and an increased risk of pressure sore formation, while reductions in arterial compliance are a contributing factor to vascular damage, and the associated risks of thrombosis, myocardial infarction and stroke. The primary purpose of this thesis was to examine the effects of exercise training on resting measures of HRV, BPV and arterial dimension and function in individuals with SCI. A secondary purpose, was to determine the effects of exervise training on the ability to tolerate orthostatic stress in individuals with SCI. Although the first training study in this thesis used arm ergometry and resistance training as the exercise stimulus, the principle mode of exercise training that was used was body-weight supported treadmill training (BWSTT) as it may be particularly well suited as a cardiovascular stimulus in the SCI population. Specifically, BWSTT is an upright exercise that involves the legs, and may be performed without the risks that are commonly associated with functional electrically stimulated (FES) exercise such as burns to the skin, stimulation-induced pain and autonomic dysreflexia. It was hypothesized that BWSTT would result in i)positive changes in the autonomic regulation of the cardiovascular system, as indicated by measures of HRV and BPC, AND II) positive changes in arterial dimension and function, as indicated by Doppler ultrasound measures. Regarding the effects of exercise training on orthostatic tolerance, previous work has provided some evidence that exercise training confers an enhanced ability for individuals with SCI to respond to cardiovascular stress. On the other hand, it was also reasonable to hypothesize that potential training-induced reductions in sympathetic outflow and arterial resistance would decrease the ability to tolerate postural stress in individuals with SCI. Methods. Short-term, continuous ECG and blood pressure (Finapres) recordings were taken before and after exercise training in individuals with SCI and used to determine measures of HRV and BPV, respectively. In addition, Doppler ultrasound imaging was performed on the femoral and carotid arteries, before and after exercise training, in order to determine vascular dimension and function. All testing was conducted in the resting supine position and during an orthostatic stress (60∘head-up tilt). Results. 1. Measures of heart rate variability (HRV) and blood pressure variability (BPV) were found to be reproducible in individuals with SCI, regardless of the level of injury. As such, clinicians and researchers may be encouraged to use these measures to determine the effectiveness of various interventions on the cardiovacular health in the SCI population. 2. Individuals with incomplete tetraplegia were found to retain the ability to make positive changes in cardiac sympathovagal balance following 3 months of combined arm ergometry and resistance exercise training. No exercise-induced changes were noted in orthostatic tolerance. 3. The results of the third study demonstrated that individuals with incomplete tetraplegia can make positive adaptation to the autonomic regulation of the cardiovascular system following 6 months of BWSTT as indicated by measures of HRV and BPV. In addition, these adaptations occurred without an accompanying tendency to become less tolerant of orthostatic stress. 4. The results of the fourth study showed that individuals with motor-complete SCI may experience favourable vascular changes following 4 months of BWSTT. Although there were no significant exercise-induced changes in measures of HRV and BPV, the results suggested that favourable changes in both these measures may occur in individuals who rexperience a substantial heart rate (HR) response to this type of training. Greater HR responses were elicited in those who were more orthostatically intolerant and had greater muscle spasticity. Finally, BWSTT was found to women worsen orthostatic intolerance in individuals with tetraplegia, but not in those with paraplegia. Conclusions. Individuals with SCI retain the ability to make positive changes in cardiovascular regulation with exercise training, as indicated by measures of HRV and BPC, as well as by Doppler ultrasound measures of arterial function. Individuals with less severe SCI (ASIA C and D injuries) may be particularly well suited for BWSTT as a means to promote cardiovascular improvement. Specifically, individuals with spared motor function (ASIA C injuries) made positive adaptations in meaures of HRV and BPC after 6 months of BWSTT, and further, due to the spared sensory ability, these individuals may not be able to tolerant FES exercise. Individuals with motor-complete SCI may experience positive vascular changes with BWSTT, regardless of the HR elicited during this form of exercise. In addition, those with high muscle spasticity and a susceptibility to orthostatic intolerance may experience positive adaptations in measures of HRV and BPV.
Keywords: Kinesiology; Kinesiology